Crown ether modified nanofiltration membrane for selective separation of lithium and magnesium and preparation method of crown ether modified nanofiltration membrane

By introducing 2-aminomethyl-18-crown-6 ether into a nanofiltration membrane and carrying out an interfacial polymerization reaction with a surfactant, a covalently bonded crown ether-modified nanofiltration membrane is generated, which solves the problems of low lithium-magnesium separation efficiency and poor stability, and achieves efficient and stable lithium-magnesium separation, suitable for the separation of high magnesium-to-lithium ratio brines.

CN120789951APending Publication Date: 2025-10-17CHANGZHOU UNIV
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202510791400.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-06-13
Publication Date
2025-10-17

AI Technical Summary

Technical Problem

Existing technologies are insufficient for efficiently and cost-effectively separating lithium and magnesium from salt lake brine. Traditional nanofiltration membranes exhibit poor stability during long-term operation and have low lithium-magnesium separation efficiency, making it difficult to meet the production requirements of high-purity lithium products.

Method used

Interfacial polymerization of 2-aminomethyl-18-crown-6 ether with surfactant and polyamine in aqueous solution was carried out to generate a covalently bonded crown ether-modified nanofiltration membrane, forming a dense polyamide separation layer to provide selective separation of lithium and magnesium.

Benefits of technology

It achieves efficient separation of lithium and magnesium, improves the separation efficiency of magnesium and lithium and the stability of the membrane, extends the service life, adapts to the separation requirements of brine with high magnesium-to-lithium ratio, and meets the requirements of continuous and stable operation in industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120789951A_ABST
    Figure CN120789951A_ABST
Patent Text Reader

Abstract

The invention discloses a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium and a preparation method of the crown ether modified nanofiltration membrane, and belongs to the technical field of membrane separation. The preparation method comprises the following steps: by taking a porous ultrafiltration membrane as a substrate and 2-aminomethyl-18-crown-6 ether and polyamine as water-phase monomers, carrying out interfacial polymerization reaction on the water-phase monomers and trimesoyl chloride on the surface of the porous ultrafiltration membrane to form a polyamide layer; wherein 2-aminomethyl-18-crown-6 ether is introduced into the polyamide separation layer in the form of a covalent bond through a reaction with trimesoyl chloride. The prepared nanofiltration membrane can effectively intercept Mg < 2 + > and provide an exclusive transport channel for Li < + >, so that the Li < + > smoothly crosses the membrane, and the lithium-magnesium separation effect is achieved. The method is simple in preparation process operation, low in energy consumption and easy to amplify, can be used for salt lake lithium extraction, and has a wide industrial application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the field of membrane separation technology, and particularly relates to a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium and a preparation method thereof. BACKGROUND

[0002] Lithium is the "white oil" in the 21st century, and has irreplaceable strategic value in the fields of new energy, energy storage batteries, and fine chemical industry. China is rich in lithium resources in salt lake brine, but there are problems such as high magnesium-lithium ratio and low lithium concentration, which leads to low efficiency, high cost and environmental pollution in traditional separation technologies such as precipitation and extraction. In addition, lithium and magnesium are adjacent elements on the diagonal, and they show similar chemical properties based on the "diagonal relationship", making it difficult to separate lithium and magnesium. Therefore, magnesium-lithium separation is the key difficulty and main obstacle for green, efficient and low-cost lithium extraction from salt lakes.

[0003] The driving mechanism of nanofiltration membranes includes Donnan effect, dielectric effect and space barrier effect, which can effectively block divalent and high valence ions, and has good permeability to monovalent ions. In addition, nanofiltration membrane technology is economic, efficient, simple, and environmentally friendly, and is considered to be a very promising magnesium-lithium separation technology.

[0004] The interfacial polymerization reaction of water phase and oil phase monomers at the interface of two phases is the most mature method for preparing thin film composite nanofiltration membranes with nanoscale pore size. However, in the traditional interfacial polymerization process, the order of amine monomer diffusion is low, which makes the distribution of monomers at the water / oil interface uneven, and further causes local differences in interfacial polymerization reaction, resulting in a problem of wide pore size distribution in the formed polyamide separation layer. Since the separation pore size of the polyamide membrane material is similar to the size of magnesium ions, when the membrane pore size distribution is wide, magnesium ions can penetrate through the large pores on the membrane surface, resulting in a decrease in magnesium ion retention rate, and therefore it is difficult to achieve precise screening of lithium / magnesium ions with similar hydrated ion sizes.

[0005] Crown ethers are introduced into the field of membrane separation due to their specific cavity structure and ion selective complexing ability. By utilizing the strong complexation of crown ethers with Mg 2+ , lithium-magnesium separation is achieved under the driving of concentration difference. However, existing crown ether membranes are mostly physically adsorbed or simply cross-linked on the membrane surface, and crown ethers are easy to fall off during long-term operation, resulting in a decrease in separation performance. In addition, the uneven distribution of polyamines in the traditional interfacial polymerization process can easily form membrane defects, affecting the denseness of the separation layer.

[0006] Although the preparation technology of nanofiltration membrane for lithium-magnesium separation is relatively mature at present, especially the positively charged nanofiltration membrane. The traditional nanofiltration membrane realizes the selective separation of lithium and magnesium ions by regulating the pore size distribution and surface charge, but its adaptability to high magnesium-lithium ratio brine is limited, which is difficult to meet the demand of high-purity lithium product production. In addition, the existing nanofiltration membrane also faces the problems of poor membrane stability and short service life in practical application, which is mainly due to the weak binding force between the membrane material and the active separation layer. In the long-term operation process, the membrane structure is easily damaged, and the separation performance is decreased. SUMMARY

[0007] This section is intended to summarize some aspects of the embodiments of the present application and briefly introduce some preferred embodiments. Some simplifications or omissions may be made in this section and the abstract and title of the specification of the present application to avoid obscuring the purpose of this section, the abstract and the title, and such simplifications or omissions cannot be used to limit the scope of the present application.

[0008] In view of the above and / or problems existing in the prior art, the present application is proposed.

[0009] Therefore, the purpose of the present application is to overcome the deficiencies in the prior art, and to provide a preparation method of crown ether modified nanofiltration membrane for lithium-magnesium selective separation.

[0010] To solve the above technical problems, the present application provides the following technical solutions, including,

[0011] 2-amino methyl-18-crown-6 ether, a surfactant, and a polyamine are dissolved in deionized water and stirred uniformly to obtain an aqueous solution;

[0012] Trimesoyl chloride is dissolved in an organic solvent and stirred uniformly to obtain an oil phase solution with a mass concentration of 0.01% to 0.25%;

[0013] The porous ultrafiltration membrane base film is immersed in the aqueous solution for surface contact. After removing the excess aqueous solution on the membrane surface, the oil phase solution is poured for interfacial polymerization reaction to form a cross-linked polyamide separation layer. After the reaction is completed, the surface residual oil phase is cleaned, and then the membrane is heat treated at 20 to 90℃ for 5 to 30 minutes, and then immersed in deionized water for 2 to 24 hours to obtain the crown ether modified nanofiltration membrane for lithium-magnesium selective separation.

[0014] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for lithium-magnesium selective separation according to the present application, the surfactant includes one or more of sodium dodecyl sulfonate, sodium dodecyl sulfonate, sodium octyl sulfonate, potassium octyl sulfonate, sodium dodecyl polyoxyethylene ether sulfate, and dodecyl polyoxyethylene ether sulfate.

[0015] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, the polyamines include one or more of piperazine, polyethyleneimine, polyhexamethylene guanidine hydrochloride, diethylene triamine, triethylene tetramine or polyethylene polyamine.

[0016] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, in the aqueous solution, the mass concentration of 2-aminomethyl-18-crown-6 ether is 0.1-1%, the mass concentration of the surfactant is 0.05-0.5%, and the mass concentration of the polyamines is 0.1%-3%.

[0017] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, the porous ultrafiltration membrane substrate has a pore size of 5-100 nm, and the material of the porous ultrafiltration membrane substrate includes polysulfone, polyethersulfone, polyacrylonitrile, zirconium oxide, aluminum oxide or titanium oxide.

[0018] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, the organic solvent includes one or more of n-hexane, cyclohexane or benzene.

[0019] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, the aqueous solution and the oil phase solution have a dissolution temperature of 20-45°C.

[0020] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, the surface contact time is 10-240 s.

[0021] As a preferred scheme of the preparation method of the crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, in the scheme, the interfacial polymerization reaction has a reaction time of 10-150 s, a reaction temperature of 10-40°C and a relative humidity of 20-80%.

[0022] Another object of the present application is to provide a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium.

[0023] The present application has the following advantages:

[0024] In the present application, the surfactant and 2-aminomethyl-18-crown-6 ether are added to an aqueous solution mainly containing polyamines, and then an interfacial polymerization reaction is performed with trimesoyl chloride to form a polyamide separation layer. The 2-aminomethyl-18-crown-6 ether is covalently bonded to the separation layer, and the unique cavity structure of the 2-aminomethyl-18-crown-6 ether allows Li + to pass through smoothly. Since the hydrated ion needs to lose water when passing through the cavity, and the Li +The dehydrated water overcomes the hydration energy far lower than Mg 2+ , so as to realize Li + efficient transportation. The membrane structure can effectively intercept Mg 2+ , and provide a dedicated channel for Li + , so as to achieve efficient separation of lithium and magnesium, and provide an innovative and practical solution for the lithium-magnesium separation problem in lithium resource development.

[0025] The nanofiltration membrane of the application has good stability and reliability during long-term operation, and can continuously maintain high lithium-magnesium separation performance, thereby providing a strong guarantee for continuous and stable operation in industrial production.

[0026] The preparation method provided by the application has simple process, high production efficiency and easy scale-up production. BRIEF DESCRIPTION OF DRAWINGS

[0027] In order to more clearly illustrate the technical solutions of the embodiments of the application, the drawings needed in the embodiment description will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the application, and other drawings can be obtained by those skilled in the art without creative labor. Among them:

[0028] Figure 1 The long-term stability test diagram of the nanofiltration membrane prepared in Example 3 of the application.

[0029] Figure 2 The surface electron microscope (SEM) diagram of the nanofiltration membrane prepared in Example 3 of the application.

[0030] Figure 3 The surface electron microscope (SEM) diagram of the nanofiltration membrane prepared in Comparative Example 1.

[0031] Figure 4 The separation performance diagram of the nanofiltration membrane prepared under different 2-aminomethyl-18-crown-6 ether concentrations. DETAILED DESCRIPTION

[0032] In order to make the above-mentioned purposes, features and advantages of the application more obvious and easy to understand, the specific embodiments of the application will be described in detail below.

[0033] In the following description, many specific details are set forth in order to provide a thorough understanding of the application, but the application can also be implemented in other ways different from those described herein, and those skilled in the art can make similar generalizations without departing from the scope of the application, therefore the application is not limited to the specific embodiments disclosed below.

[0034] Second, the "one embodiment" or "an embodiment" referred to herein means a specific feature, structure, or characteristic under discussion. Each of the various embodiments presented in this specification are not necessarily mutually exclusive, but can be selectively implemented in various embodiments of the application.

[0035] The raw materials used in the application are all commercially available.

[0036] The material prepared in the embodiment of the application is tested for performance as follows:

[0037] The nanofiltration membrane prepared by the method of the application is used to test the Mg 2+ / Li + The mixture of MgCl2 and LiCl salt with a mass ratio of 30:1 and a total salt concentration of 2000 ppm is used as model brine to test the Li + / Mg 2+ selectivity, the test temperature is 25°C, and the operating pressure is 6 bar.

[0038] The nanofiltration membrane is tested for long-term stability using a 1000 ppm MgCl2 aqueous solution, the test temperature is 25°C, the test pressure is 6 bar, and the test time is 50 h.

[0039] Embodiment 1

[0040] The embodiment provides a preparation method of a nanofiltration membrane, specifically:

[0041] (1) Dissolve 1% piperazine monomer, 0.1% sodium dodecyl sulfonate, and 0.2% 2-aminomethyl-18-crown-6 ether in water to obtain an aqueous phase solution;

[0042] (2) Dissolve trimesoyl chloride in n-hexane and stir uniformly to obtain a 0.1% trimesoyl chloride oil phase solution;

[0043] (3) Soak the polysulfone-based membrane in the aqueous phase solution, remove the excess solution on the surface of the membrane using a rubber roller after soaking for 120 s, pour the oil phase solution, and perform interfacial polymerization to form a crosslinked polyamide separation layer, pour out after 30 s, and clean the surface residual oil phase monomer with n-hexane; heat the above-mentioned membrane at 60°C for 5 min, and then soak in deionized water for 12 h to obtain a nanofiltration membrane for lithium-magnesium separation.

[0044] Embodiment 2

[0045] The difference between the embodiment and embodiment 1 is that the mass concentration of 2-aminomethyl-18-crown-6 ether in the aqueous phase solution is adjusted to 0.4%, and the rest of the preparation process is the same as that of embodiment 1 to prepare a nanofiltration membrane.

[0046] Example 3

[0047] The difference between this example and Example 1 is that the mass concentration of 2-aminomethyl-18-crown-6 ether in the aqueous solution is adjusted to 0.6%, and the rest of the preparation process is the same as that of Example 1, and a nanofiltration membrane is prepared.

[0048] Figure 1 The long-term stability test diagram of the nanofiltration membrane prepared in this example can be seen that the MgCl2 rejection rate still maintains 97% after 50h continuous test. Figure 2 The SEM diagram of the nanofiltration membrane prepared in this example can be seen that after adding sodium dodecyl sulfonate and 2-aminomethyl-18-crown-6 ether, the surface morphology of the membrane changes and presents strip-shaped protrusions.

[0049] Example 4

[0050] The difference between this example and Example 1 is that the mass concentration of 2-aminomethyl-18-crown-6 ether in the aqueous solution is adjusted to 0.8%, and the rest of the preparation process is the same as that of Example 1, and a nanofiltration membrane is prepared.

[0051] Comparative Example 1

[0052] The difference between this comparative example and Example 1 is that the contents of sodium dodecyl sulfonate and 2-aminomethyl-18-crown-6 ether in the aqueous solution are adjusted to 0, and the rest of the preparation process is the same as that of Example 1, and a nanofiltration membrane is prepared.

[0053] Comparative Example 2

[0054] The difference between this comparative example and Example 1 is that the content of 2-aminomethyl-18-crown-6 ether in the aqueous solution is adjusted to 0, and the rest of the preparation process is the same as that of Example 1, and a nanofiltration membrane is prepared.

[0055] The nanofiltration membranes prepared in the above examples and comparative examples are tested for performance, and the comparison results with Example 3 are shown in Table 1.

[0056] Table 1

[0057]

[0058]

[0059] From the above table, it can be seen that adjusting the addition amount of 2-aminomethyl-18-crown-6 ether has a significant effect on the performance of the nanofiltration membrane. This is because after adding 2-aminomethyl-18-crown-6 ether, the membrane not only has a narrowed pore size structure, but also has a lithium ion channel, so that not only can magnesium ions be effectively intercepted, but also lithium ions can pass through smoothly. According to the results in the above table, the best technical effect can be obtained when the mass concentration of 2-aminomethyl-18-crown-6 ether in the aqueous phase solution in the present application is 0.6%.

[0060] Figure 2 The SEM image of the nanofiltration membrane prepared for Example 3 of the present application is shown in the following figure, Figure 3 The SEM image of the nanofiltration membrane prepared for Comparative Example 1 is shown in the following figure. In combination with the above table and Figures 1 to 4 It can be seen that the membrane prepared in Comparative Example 1 has large pores and does not have lithium-magnesium separation ability due to the negative charge on the membrane surface. The membrane prepared in Comparative Example 2 has a narrowed pore structure, so the interception rate of Mg 2+ is large, but it does not have a lithium ion channel, so the permeation rate of Li + is low, although it has a certain lithium-magnesium separation ability, but the practical application ability is low. After adding sodium dodecyl sulfonate and 2-aminomethyl-18-crown-6 ether, Figure 2 and Figure 3 It can be seen that the surface morphology of the nanofiltration membrane prepared in Example 3 changes and presents a striped protrusion. In the present application, the surfactant and 2-aminomethyl-18-crown-6 ether are added to the aqueous phase solution mainly containing a polyamine, and then an interfacial polymerization reaction is carried out with trimesoyl chloride to generate a polyamide separation layer. The 2-aminomethyl-18-crown-6 ether is covalently bonded to the separation layer, and its unique cavity structure can allow Li + to pass through smoothly. Since the hydrated ion needs to lose water of hydration when passing through the cavity, and the hydration energy overcome by Li + is much lower than that of Mg 2+ , so efficient transportation of Li + is achieved. This membrane structure can effectively intercept Mg 2+ , and provides a dedicated channel for Li + , achieving efficient separation of lithium and magnesium.

[0061] Example 5

[0062] The difference between this example and Example 3 is that the mass concentration of piperazine monomer in the aqueous phase solution is adjusted to 0.5%, and the rest of the preparation process is the same as that of Example 3, and a nanofiltration membrane is prepared.

[0063] Example 6

[0064] The difference between this example and Example 3 is that the mass concentration of sodium dodecyl sulfonate in the aqueous phase solution is adjusted to 0.05%, and the rest of the preparation process is the same as that of Example 3, and a nanofiltration membrane is prepared.

[0065] The performance of the nanofiltration membranes prepared in the above examples and comparative examples was tested, and the results of the comparison with Example 3 are shown in Table 2.

[0066] Table 2

[0067]

[0068]

[0069] As can be seen from the above table, adjusting the addition amount of the piperazine monomer has a significant effect on the performance of the nanofiltration membrane, because the change in the concentration of the piperazine monomer affects the chemical structure and pore size distribution of the cross-linked polyamide separation layer, and in turn affects the separation selectivity of the nanofiltration membrane for lithium and magnesium ions. If the concentration of the piperazine monomer is too high, it can cause the pore size distribution of the membrane to be uneven, reducing the separation selectivity for lithium and magnesium ions. If the concentration is too low, it can cause the pore size of the membrane to be too large, and the lithium and magnesium ions cannot be effectively separated. According to the results in the above table, the best technical effect can be obtained when the mass concentration of the piperazine monomer in the aqueous phase solution is 1% in the present application.

[0070] In summary, the cyclic molecular crown ether derivative 2-aminomethyl-18-crown-6 ether with a cavity structure is introduced into an aqueous phase solution mainly containing a polyamine in a covalent bond manner, and a polymerization reaction is carried out with trimesoyl chloride to generate a polyamide nanofiltration membrane separation layer with a dense structure, so that the prepared nanofiltration membrane can effectively retain Mg 2+ , and provide a Li + exclusive transport channel, achieving the effect of lithium-magnesium separation.

[0071] The nanofiltration membrane prepared in the present application has the following excellent performance:

[0072] Significantly improve the lithium-magnesium separation efficiency: the present application introduces a crown ether group into the nanofiltration membrane, utilizes the strong complexation of the crown ether with Mg 2+ and the exclusive channel characteristics of the crown ether for Li + , and realizes efficient separation of lithium and magnesium ions. In the test of a Mg 2+ / Li + mass ratio of 30:1, a total salt concentration of 2000 ppm of a mixture of MgCl2 and LiCl salt as model brine, the rejection rate of Mg 2+ is as high as 95.9%, the rejection rate of Li + is -41.1%, and the separation factor reaches 34.6. This result shows that the nanofiltration membrane of the present application can effectively retain Mg 2+ , while allowing Li + to pass through the membrane layer smoothly, significantly improving the lithium-magnesium separation efficiency, and solving the problem that traditional separation technologies cannot achieve efficient separation of lithium and magnesium.

[0073] Excellent long-term stability: In the long-term stability test of 1000 ppm MgCl2 aqueous solution, the test temperature is 25℃, the test pressure is 6bar, and the MgCl2 retention rate is maintained at 97% after 50h continuous test. This indicates that the nanofiltration membrane of the present application has good stability and reliability during long-term operation, and can continuously maintain high-efficiency lithium-magnesium separation performance, providing strong guarantee for continuous and stable operation in industrial production.

[0074] Unique crown ether modified structure: The crown ether group is introduced into the polyamide separation layer in the form of a covalent bond in the present application, forming a unique crown ether modified nanofiltration membrane structure. This structure not only endows the membrane with excellent lithium-magnesium separation performance, but also solves the problem that the existing crown ether membrane is easily detached and the separation performance decreases during long-term operation because the crown ether is usually fixed on the surface of the membrane by physical adsorption or simple crosslinking. The firm combination of the crown ether group and the polyamide separation layer enhances the structural stability of the membrane and prolongs the service life of the membrane.

[0075] Optimized pore size distribution and membrane layer structure: The polyamide separation layer prepared by interfacial polymerization has a dense structure and uniform pore size distribution. The present application regulates the pore size and distribution of the polyamide separation layer, so that it can more accurately realize the screening of lithium-magnesium ions. In addition, the introduction of crown ether group also provides a dedicated transport channel for Li + , reduces the transport resistance of Li + , improves the permeation performance of the membrane, and realizes the dual optimization of lithium-magnesium separation performance and membrane flux.

[0076] It should be noted that the above examples are only used to illustrate the technical solutions of the present application and not to limit it. Although the present application has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present application can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present application, and they should be covered in the scope of the claims of the present application.

Claims

1. A method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium, characterized in that: include, Dissolve 2-aminomethyl-18-crown-6 ether, surfactant, and polyamine in deionized water and stir evenly to obtain an aqueous solution; Dissolve trimesoyl chloride in an organic solvent and stir evenly to obtain an oil phase solution with a mass concentration of 0.01% to 0.25%; The porous ultrafiltration membrane base membrane is immersed in an aqueous solution for surface contact. After removing excess aqueous solution from the membrane surface, an oil phase solution is poured to perform interfacial polymerization to form a cross-linked polyamide separation layer. After the reaction is completed, the residual oil phase on the surface is cleaned and then heat-treated at 20-90°C for 5-30 minutes. After the heat treatment is completed, the membrane is soaked in deionized water for 2-24 hours to obtain a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium.

2. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The surfactant includes one or more of sodium lauryl sulfate, sodium lauryl sulfate, sodium octyl sulfate, potassium octyl sulfate, sodium dodecyloxyethanol sulfate, and dodecyl polyoxyethylene ether sulfate.

3. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The polyamine includes one or more of piperazine, polyethyleneimine, polyhexamethyleneguanidine hydrochloride, diethylenetriamine, triethylenetetramine or polyethylenepolyamine.

4. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, 2 or 3, wherein: In the aqueous phase solution, the mass concentration of 2-aminomethyl-18-crown-6 ether is 0.1-1%, the mass concentration of the surfactant is 0.05-0.5%, and the mass concentration of the polyamine is 0.1%-3%.

5. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The pore size of the porous ultrafiltration membrane substrate is 5 to 100 nm, and the material of the porous ultrafiltration membrane substrate includes polysulfone, polyethersulfone, polyacrylonitrile, zirconium oxide, aluminum oxide, and titanium oxide.

6. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The organic solvent includes one or more of n-hexane, cyclohexane, and benzene.

7. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The dissolution temperature of the aqueous phase solution and the oil phase solution is 20-45°C.

8. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The surface contact time is 10 to 240 seconds.

9. The method for preparing a crown ether modified nanofiltration membrane for selective separation of lithium and magnesium according to claim 1, wherein: The interfacial polymerization reaction has a reaction time of 10 to 150 seconds, a reaction temperature of 10 to 40° C., and a relative humidity of 20 to 80%.

10. A crown ether modified nanofiltration membrane for selective separation of lithium and magnesium prepared by the preparation method according to any one of claims 1 to 3 and 5 to 9.

Citation Information

Cited By

  • Separation system and process suitable for lithium battery wastewater

    CN121202391A

  • Crown ether modified positively charged polyamide / carbon nanotube nanofiltration membrane as well as preparation method and application thereof

    CN122273334A